1984
DOI: 10.1002/app.1984.070291135
|View full text |Cite
|
Sign up to set email alerts
|

Radial temperature differences during the melt spinning of fibers

Abstract: SynopsisIn this investigation, a numerical model was developed to predict the temperature distribution in a fiber during melt spinning. This model uses the implicit Crank-Nicolson method to solve the governing differential equation for the problem. The model was applied to a series of numerical experiments on a liquid crystalline fiber which is melt-spun. These simulations used typical sets of operating conditions to determine the effect of various operating parameters on the predicted radius profile, spinline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Crank-Nicolson method [14] is used to solve equation (20). A Q × M 2-D finite difference grid is created along the fiber axis crossing the fiber center, covering the domain of 0 ≤ ξ ≤ 1 and 0 ≤ ζ ≤ 1, as shown in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Crank-Nicolson method [14] is used to solve equation (20). A Q × M 2-D finite difference grid is created along the fiber axis crossing the fiber center, covering the domain of 0 ≤ ξ ≤ 1 and 0 ≤ ζ ≤ 1, as shown in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming (a) constant physical properties of density, specific heat capacity, and thermal conductivity of melt, (b) negligible radial crystallinity and orientation distributions, the 2-D governing equation of energy reads [14] (20)…”
Section: -D Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation parameters are the material and rheological properties of the polymer, the screw, hopper and die geometry, and the operating conditions (screw speed and barrel temperature profile). Hutchenson et al [4] developed a numerical model to predict the temperature distribution in a fiber during melt spinning. The results of the various runs showed that ambient air temperature and mass flow rate had a significant effect on the predicted radius profile, spinline tension, and temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming predetermined values at the boundary and using a finite difference method, Edie and coworkers [11,12] analyzed the radial distribution of internal stress and temperature. Simple mathematical model utilizing 1dimensional formulation has been recently developed to investigate this process with heat conduction and radiation effects [13].…”
Section: Introductionmentioning
confidence: 99%